BRANDING MUKENA YABASMAH MELALUI MEDIA SOSIAL TIKTOK (STUDI ANALISIS KUALITATIF AKUN @YABASMAH.BWI) - elvina febriyanti; Agus Baihaqi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
@Yabasmah.Bwi in promoting the Yabasmah mukena product. In today‘s digital era, social media—particularly TikTok—has become an effective platform for introducing products, building brand image, and engaging with a wider audience in a creative and interactive manner. Yabasmah mukena, as a religious fashion product for Muslim women, utilizes this platform to strengthen its brand identity and increase consumer interest as well as attract potential resellers. This study uses a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The research subjects include the head of the Yabasmah Banyuwangi agency, social media admins, and both online and offline consumers. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that the branding strategy on TikTok includes the use of creative content, live streaming sessions, and various engaging features aligned with audience trends. Content that highlights product uniqueness, customer testimonials, and communicative delivery helps boost brand awareness and audience engagement. Branding via TikTok has also proven effective in attracting new resellers and expanding the market reach of the Yabasmah mukena. This research concludes that TikTok as a branding platform significantly contributes to shaping a positive brand image and expanding product distribution for Yabasmah mukena amid the competitive Muslim fashion industry.